Impacts of hazardous noise levels on hearing loss and tinnitus in dental professionals - Celia Zhang; Andrew Young; Samantha Rodriguez; Karen A. Schulze; Bina Surti; Fadi Najem; Jiong Hu (Journal of Occupational Medicine and Toxicology, 2025)
Abstract Background Hazardous noise exposure is an important health concern in many workplaces and is one of the most common work-related injuries in the United States. Dental professionals are frequently exposed to high levels of occupational noise in their daily work environment. This noise is generated by various dental handpieces such as drills, suctions, and ultrasonic scalers. Prolonged exposure to such noise levels is known to have adverse effects on hearing health. Despite the prevalence of occupational noise in dentistry, there is a paucity of research specifically examining the prevalence of hearing loss and tinnitus in dental professionals. Methods To evaluate the prevalence of hearing loss and tinnitus, data were collected from 60 dental professionals, including participant demographics and audiometric thresholds. Thresholds were compared to the age- and sex-based reference ranges from the International Standards Organization (ISO 7029:2017). Results Results showed that 15–25% of males and 13–18% of females had hearing thresholds that exceeded 95th percentile limits based on the ISO normative age- and sex-distributions. Tinnitus was reported in 40% of the participants. Conclusion This study is the first to examine the characteristics and prevalence of auditory dysfunctions in dental professionals compared to the ISO normative age and sex distributions of hearing status. Findings from this study highlight the need for increasing the awareness of occupational noise hazards among dental professionals and the importance of routine audiological monitoring.